Prestando acuerdo: El Senado frente a los nombramientos del Poder Judicial en la Argentina democrática (1983-2006); The Senate and the President: Judicial Nominations in Democratic Argentina (1983-2006) - Mariana Llanos; Constanza Figueroa Schibber (German Institute of Global and Area Studies (GIGA), 2007)
This article aims to evaluate to what extent the Argentine Senate was able to fulfil its constitutional function of controlling the Executive's prerogative to nominate judges between 1983 and 2006, as well as to examine the factors that influenced the exercise of this role. To do so, the paper focuses on the parliamentary procedure of the proposals submitted by the Executive for the nomination of all federal judges, the members of the so-called 'national justice' of Buenos Aires and those of the Public Ministry. The findings show that the Senate's powers depend on several factors, such as, the institutional resources with which presidents count in this chamber (which includes not only the size of the parliamentary majority but also their power in the Committee of Acuerdos), the category of the position to be filled (whether involving Supreme Court justices or not), presidential ambitions in other policy areas (such as re-election), and the rules regulating the selection and confirmation of candidates (such as the secrecy or publicity of the legislative process). – – Der Artikel analysiert, in welchem Maß der argentinischen Senat zwischen 1983 und 2006 in der Lage gewesen ist, seine verfassungsmäßige Funktion als Kontrollorgan bei der Nominierung von Richtern durch die Exekutive auszuüben. Dabei wird auch nach den Faktoren gefragt, die die Ausübung dieser Rolle beeinflussten. Zu diesem Zweck untersucht die Studie die parlamentarischen Verfahren bei den von der Exekutive unterbreiteten Kandidaten für alle Bundesrichter, die Mitglieder der sogenannten 'nationalen Justiz' von Buenos Aires sowie der Staatsanwaltschaft. Die Ergebnisse zeigen, dass die Macht des Senats von einer Reihe von Faktoren abhängt, unter anderem von den institutionellen Ressourcen des Präsidenten in dieser Kammer (was nicht nur die Größe der Parlamentsfraktion umfasst, sondern auch ihre Macht in der Verhandlungskommission), der Art der zu besetzenden Stelle (ob es sich um den Obersten Gerichtshof handelt oder nicht), den Ambitionen des Präsidenten in anderen Politikfeldern (z.B. Wiederwahl) sowie den bestehenden Regeln über Auswahl und Bestätigung von Kandidaten (z.B. ob das Verfahren öffentlich oder nicht-öffentlich erfolgt).
Keywords: 300; judicial appointments; presidential nominations; senatorial confirmations; Argentine Supreme Court; Argentine lower courts